Mass Drug Administration for Lymphatic Filariasis Elimination in Two Districts of North Karnataka: Coverage and Compliance Assessment - Huluvadi Shivalingaiah Anwith; S R Suhas; Seema K S; Karishma P S; K Ravi Kumar; Madhusudhan M (Indian Association of Preventive and Social Medicine, 2020)
Introduction: Lymphatic filariasis or elephantiasis is the most debilitating and disfiguring scourge among all diseases which imposes severe social and economic burden. Currently an estimated 63crores people are at a risk of filariasis in 256 endemic districts across 16 states and 5 union territories in India. National filarial control programme is operational since 1955 in India and the current goal is achieving elimination of filariasis by 2020through Mass Drug Administration (MDA). Objective: To assess the coverage, compliance and causes for noncompliance of MDA in the study districts. Method: A cross sectional descriptive study was conducted in October 2019 and January 2020 in Koppal and Bidar districts respectively. Randomly four clusters were selected, three from rural area and one from urban area. All the residents of a cluster were included except subjects aged below 2 years and pregnant women. Data collection was done by household survey using a standard questionnaire. Results: Total populations of 2043 subjects residing in 480 houses were included. The coverage rate was95.44 &94.73% with compliance rate of 91.61% &93.12% in Koppal & Bidar districts, respectively. The effective coverage rate was 87.44 %& 88.2% in Koppal & Bidar districts respectively. Drug consumption by DOT was 95.1% in Koppal&85.8% in Bidar district. Conclusions: The coverage& compliance of MDA was found to be satisfactoryas it was >65%.Consumption of MDA by DOT to be more emphasized to reduce coverage compliance gap and increase the effective coverage rate.